Role of goat in transmission of schistosomiasis japonica Ⅳ Schistosome development in goat and egg count and distribution in goat feces - Xue-Hui, Shen; Jian-Rong, Dai; Le-Ping, Sun; Zhong-Yu, Fu; Ye-Fang, Li; Guo-Li, Qu; Wei, Wang; Yun-Tian, Xing; Yi-An, Wang; You-Sheng, Liang (Zhongguo xue xi chong bing fang zhi za zhi, 2016)
To describe the growth and development of in goat and the intensity and temporal distribution of eggs excreted by goat feces, so as to provide baseline data for the control and elimination of the role of goat in the transmission of schistosomiasis. The goat animal models of schistosomiasis were established, and stool samples were collected for parasitological examinations. The number of adult worms recovered, variation of schistosomes in goat at different time points post-infection, number of eggs in schistosomes, variation in number and temporal profiles of eggs excreted from goat feces were observed. Of the 6 schistosome-infected goat, 415 adult worms were recovered, with a mean adult worm recovery of 34.58% (range, 23.00% to 45.50%). Among the 5 goat infected with 200 cercariae each, 47, 93, 77, 74 and 73 adult worms were recovered 2, 5, 8, 11 and 14 months post-infection, respectively. There were (200.00±42.33), (226.20±45.88), (168.20±25.85), (183.80±55.13) and (190.80±53.53) eggs detected in female schi